Engineered asparaginase from Erwinia chrysanthemi enhances asparagine hydrolase activity and diminishes enzyme immunoreactivity - a new promise to treat acute lymphoblastic leukemia - Munhoz Costa, Iris; Custódio Moura, Débora; Meira Lima, Guilherme; Pessoa, Adalberto; Oresco dos Santos, Camila; de Oliveira, Marcos A [UNESP]; Monteiro, Gisele (Wiley, 2022)
BACKGROUND: The treatment of acute lymphoblastic leukemia (ALL) uses the biopharmaceutical l-asparaginase (ASNase) as the main medication. This drug, from bacterial origin (Escherichia coli or Erwinia chrysanthemi), depletes l-asparagine (Asn) and secondarily l-glutamine (Gln – GLNase activity) from the bloodstream, leading leukemic cells to die by deprivation of Asn. The use of ASNase is limited by the high incidence of adverse effects, which collectively can specifically impair quality of life of patients. Its high toxicity caused by the product of the hydrolysis of amino acids and the formation of anti-ASNase antibodies often required treatment interruption, thus reducing the chances of cure and increasing the rates of disease relapse. RESULTS: In order to improve enzymatic activity, while reducing toxicity, we developed through directed evolution a double-mutant ASNase from Erwinia chrysanthemi (Erw_DM), which has specific activity for Asn 46% higher than the wild-type enzyme (Erw_WT). This makes it possible to reduce the amount of protein necessary for depletion of this amino acid and, consequently, the reduction of GLNase activity, considered toxic. In silico analysis showed that a lower number of epitopes was exposed, resulting in reduced recognition of the recombinant protein by antibody anti-ASNase observed in vitro assay. Furthermore, we observed the same cytotoxic profile for the MOLT-4 and REH ALL cell lines using 40% lower protein mass of Erw_DM to achieve the minimum enzyme activity required in the bloodstream during treatment. CONCLUSION: Altogether, our findings describe a potent and less immunogenic ASNase, an improvement that may alleviate treatment adverse effects developed in anti-ALL therapy. © 2021 Society of Chemical Industry (SCI).
Keywords: Erwinia chrysanthemi; immunogenic epitopes; l-asparaginase; lower therapeutic ASNase dose; mutation; protein engineering